Design and Implementation of a Centralized Mosque Management Portal for Masjid Angullia (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The researchers developed the Centralized Mosque Management Portal for Masjid Angullia to improve the administration and dissemination of information within the mosque. Traditional management practices at Masjid Angullia rely on manual methods such as paper-based records, social media postings, and spreadsheets, which often lead to delays in communication, disorganized records, and increased administrative workload. To address these challenges, the study proposes a centralized web-based portal that integrates essential mosque management functions into a single digital platform. The system provides an organized and accessible hub for managing announcements, prayer schedules, events, and donation records, specifically optimized to minimize the workload for a single administrative user. It aims to enhance operational efficiency, transparency, and community engagement by systematically managing information and enabling mosque members to conveniently access updates. To meet the immediate needs of the community, the development process utilized an accelerated deployment timeline, rapidly transitioning from the initial design and foundational chapters directly to implementation and evaluation. The system was evaluated using the ISO/IEC 25010 software quality model, focusing on functionality, usability, reliability, performance efficiency, and maintainability. Evaluation results indicated that the developed portal is highly effective in supporting mosque operations. Overall, the study demonstrates that implementing a centralized digital solution enhances administrative efficiency, strengthens communication, and supports better community engagement within Masjid Angullia.